Thermodynamic Analysis of Gravitational Field Equations in Lyra Manifold - H. Moradpour; N. Sadeghnezhad; S. Ghaffari; A. Jahan (Advances in High Energy Physics)
Considering the Einstein field equations in Lyra manifold and applying the unified first law of thermodynamics as well as the Clausius relation to the apparent horizon of FRW universe, we find the entropy of apparent horizon in Lyra manifold. In addition, the validity of second law of thermodynamics and its generalized form are also studied. Finally, we use the first law of thermodynamics in order to find the horizon entropy of static spherically symmetric spacetimes. Some results of considering (anti)de-Sitter and Schwarzschild metrics have also been addressed.